FAKTOR KEUANGAN DIANTARA FAKTOR-FAKTOR PENENTU PENGEMBANGAN KLASTER IKM ROTAN - Rika Desiyanti (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2018)
.Rattan commodity are commodities who could be developed. Cluster Strategies used to develop small and medium Industry Rattan in Padang city in order to have the competitiveness and becomes a formidable industry. This study examines the factors of cluster strategies are influential on the development of the industry significantly. Those factors include: internal networks and partnerships, entrepreneurship, skills management, availability of the physical infrastructure, the quality of local government support, the quality of the support of large companies, research and development, quality support the association of industry and commerce, financial/access to business financing, availability of transportation services, and access marketing output. The object of the research was a small rattan industry cluster Padang city which is located in the Tanah Sirah Pitameh sub district of Lubuk Begalung Gadut, and Bandar Buat Padang. The research of using primary data i.e. field observations, interviews and questionnaires as well as the spread of secondary data obtained through agencies associated with the research. To answer the issue raised was used the method of multiple regression analysis. The results of field research through the dissemination of the close questionnaire and open questionnaire. There are 10 influential variables are not significantly while the influential financial variables significantly to the success of the rattan industry development.